Hybrid System Power Generation'wind-photovoltaic' Connected to the Electrical Network 220 kV - Mida Dris; Benattous Djilani (International Journal of Applied Power Engineering (IJAPE), 2018)
Renewable energy have the potential to generate electricity cleanly without pollution and a lesser dependence of resources for this production of electric power by these systems sources such as solar, wind, hydro, geothermal and biomass instead anti-environmental conventional systems such as gas, coal and oil is a remarkable idea but not frequent in Algeria. Our research focuses on the study of a hybrid energy system (Photovoltaic-Wind), connected to the Electrical Network 220 kV and this by tracking the maximum power point (MPPT) for two energy sources. For this, methods based on optimization algorithms were used side PV array and Wind turbine. With regard to the wind turbine, optimization was based on an analytical approach method. The Matlab/Simulink  is used for simulated power output from Hybrid System, power delivered to or from grid and phase voltage of the inverter leg